Assessing the Health Literacy Level of Mothers of Under 5-year-old Children With Malnutrition - Samira Bashirian; Simin Esmaeilpour-Zanjani (Journal of Holistic Nursing and Midwifery)
Introduction: Health literacy is defined as the ability to read, understand, and utilization of the basic health information to lead a better and healthy life. Low health literacy has a direct relationship with lower health and increased hospitalization. Objective: This study is aimed to investigate the health literacy level in mothers of children under the age of 5 years suffering from malnutrition in families and been supported by the health centers in Bojnourd City, Iran. Materials and Methods: This cross-sectional and analytical study, using cluster sampling method, was performed on 448 mothers with malnourished children under 5 years of age. Malnutrition in children depends on three indicators of weight-for-age, weight-for-height and height-for-age to determine their underweight, wasting and stunting status. To measure the level of health literacy in mothers, the test for functional health literacy in adults was employed. Data were analyzed using descriptive statistics and Kruskal-Wallis statistical test. Results: Based on the study results, the prevalence of underweight, stunting, and wasting of children were 83.9%, 7.1% and 8.9%, respectively. The average health literacy score of mothers was 66.98% out of which 32.1% had an inadequate level of health literacy. Comparison of the mean of health literacy scores by Kruskal-Wallis test showed that mothers with occupation and education had different levels of health literacy while mothers who were employees with a university degree had significantly higher levels of health literacy (P=0.001). Conclusion: Increasing the health literacy in mothers may be an effective way to prevent malnutrition among children. Most of the mothers in this study had an adequate level of health literacy, and the percentage of mothers with inadequate and marginal health literacy was also in considerable number. Given the importance of the health literacy, it seems necessary to have more concern and attention in this regard.